ACTINOMYCIN-D DOWNREGULATES SOX-2 AND REDUCES TUMOUR GROWTH IN A PRE-CLINICAL MODEL OF GLIOBLASTOMA. (3rd October 2018) - Taylor, Jessica; Pandele, Alina; Forte, Gabriella; Parker, Helen; Elvin, Mark; Dickson, Alan; Mcbain, Catherine; Bigger, Brian
Abstract: BACKGROUND: Actinomycin-D (ACTD) is antineoplastic antibiotic and is used to treat a variety of childhood cancers, including neuroblastoma. Few studies have investigated the efficacy of ACTD in high grade glioma; however our 3D-high throughput assay system has identified ACTD to be highly cytotoxic over a panel of twelve patient-derived glioma stem-like cell lines (GSCs). Here, we validate ACTD as a potential repurposed therapeutic for glioblastoma through the use of three-dimensional GSC culture and a patient-derived xenograft (PDX) model of glioblastoma. METHODS: Patient-derived GSCs were stably transduced with luciferase-expressing lentivirus to allow for reproducible in vivo assessment of orthotopic brain tumours by bioluminescence imaging (BLI). GSCs were treated in vitro with ACTD at established IC50 concentrations. Downregulation of SOX-2, a stem cell transcription factor, was investigated via western blot in cell lysates and through immunohistological assessment of murine brain tissue. RESULTS: Tumour growth in a recurrent PDX orthotopic model was tracked via BLI over a period of eight weeks. Treatment with ACTD was shown to significantly reduce tumour growth in a recurrent GBM PDX model, when compared to the current standard of care, temozolomide. We also demonstrate that ACTD specifically down-regulates the expression of SOX-2 both in vitro and in vivo. CONCLUSION: These findings indicate that ACTD could deplete the cancer stem-cell population within the tumour mass, ultimately leading to a delay in tumour progression.